Technology as Teacher: Digital Media and the Re-Schooling of Everyday Life (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
Drawing on examples from my phenomenological inquiries of teachers and students using new media technologies, I propose that software is our new hidden curriculum, imperceptibly re-mediating our perceptions and gestures and thereby re-schooling both adults and children in new modalities of knowing, doing, and being in the world. The truth is that there are no things, only physiognomies. (Merleau-Ponty, 1963/1983: p168)